2009
DOI: 10.1071/wf08084
|View full text |Cite
|
Sign up to set email alerts
|

The wildland fuel cell concept: an approach to characterize fine-scale variation in fuels and fire in frequently burned longleaf pine forests

Abstract: In ecosystems with frequent surface fire regimes, fire and fuel heterogeneity has been largely overlooked owing to the lack of unburned patches and the difficulty in measuring fire behavior at fine scales (0.1–10 m). The diverse vegetation in these ecosystems varies at these fine scales. This diversity could be driven by the influences of local interactions among patches of understorey vegetation and canopy-supplied fine fuels on fire behavior, yet no method we know of can capture fine-scale fuel and fire meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(142 citation statements)
references
References 39 publications
6
136
0
Order By: Relevance
“…Also, it does not provide a 3D biomass distribution. Calibration of TLS has also been used for fuel and fire effect characterization [25][26][27][28], but never in the past for leaf biomass estimation at plot scale.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it does not provide a 3D biomass distribution. Calibration of TLS has also been used for fuel and fire effect characterization [25][26][27][28], but never in the past for leaf biomass estimation at plot scale.…”
Section: Introductionmentioning
confidence: 99%
“…Reich et al [20] evaluated the spatial variability of several fuel components over a large landscape in the US Black Hills and found that the variability was governed by topography and vegetation. Hiers et al [21] measured small-scale variations in surface fuel using LiDAR and found that fuelbed depths become spatially independent after small distances (~0.5 m 2 ). Spatial variability of grasslands have been described in the context of population dynamics and restoration potential but have not been related to fuel characteristics [22].…”
Section: Introductionmentioning
confidence: 99%
“…Strip head fires were then set perpendicular to the wind, starting on the downwind end of the unit and moving upwind. Fires were initiated 30-50 m apart depending on fuel patterns, local weather conditions, and fire behavior [33]. We limit our discussion of fire in this manuscript due to the short-duration, limited response these systems have shown to fire [20].…”
Section: Study Sitesmentioning
confidence: 99%